ANALISIS KINERJA EMBUNG OELOMIN - Bunganaen, Wilhelmus (Jurnal Teknik Sipil, 2013)
Oelomin dam is one of the small dams located in Oelomin village Nekamesa Subdistict Kupang Regency. This dam was built in 1993, in order to overcome the lack of water shortage which happened in the village. According to the observation, the dam has become not as useful as it was before, for the sake of water usage. Therefore, the purpose of this research is to discover the function of the Oelomin dam from the physical, the functional, the operational and maintenance point of view. The method used is survey method and descriptive analysis, which only illustrates the research result by giving a certain value to every variable or aspect according to the likert scale. The result analysis, has showed the physical aspect value is 2.38, this explains that physically, the dam is not fully functioned yet, the functional aspect is 3.10, this explains that the function of the dam is optimized by the society, the operational and maintenance aspect is 1.49 which explains that operationally and the maintenance of the dam is in great condition. Generally, according to analysis the Oelomin dam is not in great condition with the value 2.32